How accurately are household surveys measuring the size and inequalities for the LGBT population in Bogota, Colombia? Evidence from a list experiment - Andrés Ham; Angela Guarin; Juanita Ruiz (Inter-American Development Bank (IDB), 2023)
This paper studies whether household surveys precisely identify the LGBT population and are suitable to measure labor market discrimination in Colombia. We first quantify the size of the LGBT population and estimate labor market inequalities from these data, highlighting potential pitfalls from using this approach. We then present findings from a list experiment in Bogotá, Colombia. Results show that household surveys underestimate the size of the LGBT population and may yield biased estimates of labor market inequalities. While survey estimates range between 1-4%, we find that LGBT people constitutes around 12-22% of the total population. We find heterogeneous reporting by sex, age groups, educational attainment, and marital status. Our findings suggest that while current measurement practices are a step forward for the LGBT population's statistical visibility, additional steps are required before household surveys may be used to consistently estimate discrimination and guide policy responses to protect this population.
Keywords: C90; D10; J10; J21; J70; 330; LGBT population; measurement; discrimination; household surveys; list experiment